PENGARUH PEMBERIAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN TANAMAN PAKCOY (Brassica rapa L.) PADA LAHAN KRITIS DI KECAMATAN DUMOGA UTARA KABUPATEN BOLAANG MONGONDOW - Ni Nyoman Suriantini; Joice M.J. Supit; Rafli I. Kawulusan (Universitas Sam Ratulangi, 2021)
ABSTRACT This study aims to determine the effect of cow manure application on the growth of Pakcoy (Brassica rapa L.) on critical land in North Dumoga District, Bolaang Mongondow Regency. The study was conducted in a pot experiment with cow manure treatment consisting of 0 tons/ha as control, 15 tons/ha; 30 tons/ha; 45 tons/ha and Phonska 300 kg/ha. Number of plants per hole 2 plants. The incubation period for cow manure is 1 week. Research time for 2 months. The research method was an experiment with a completely randomized basic design (CRD) and 3 replications. The variables observed were plant height, number of leaves, and wet weight of pakcoy plants. Statistical testing for data that has been tabulated using Analysis of Diversity Fingerprint (Anova) and Analysis of the Least Significant Difference Test (BNT). The results of the study showed that the cow manure treatment had a significant effect on plant height, number of leaves and wet weight of pakcoy plants. The application of cow manure in the P3 treatment (45 tons/ha) gave the highest yield on plant height, number of leaves, and wet weight of pakcoy plants. Keywords : Cow Manure, Pakcoy, Critical Land